2019
DOI: 10.1021/acs.analchem.9b01805
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich-Structured Upconversion Nanoprobes Coated with a Thin Silica Layer for Mitochondria-Targeted Cooperative Photodynamic Therapy for Solid Malignant Tumors

Abstract: Upconversion nanoparticles-based photodynamic nanotheranostic agents (UCNPs-PDT) have received great interest due to improved tissue penetration, weak autofluorescence, and low biotoxicity. However, conventional UCNPs-PDT are often limited by low energy transfer efficiency from UCNPs to photosensitizer (PS) molecules and insufficient generation and limited diffusion distance of reactive oxygen species (ROSs). Herein, an “all in one” nanotheranostic agent has been developed which has multicolor sandwich-structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Owing to the high stability, low cost, and convenient labeling, nanoparticles can also serve as signal probes for DNA detection to further improve the performance of sandwich assays [106][107][108][109][110][111][112][113][114][115]. For example, Zhang et al [116] reported a nanoparticle based "sandwich" detection strategy by immobilizing gold nanoparticles (AuNPs) with reporter probes that flank the target nucleic acids.…”
Section: +mentioning
confidence: 99%
“…Owing to the high stability, low cost, and convenient labeling, nanoparticles can also serve as signal probes for DNA detection to further improve the performance of sandwich assays [106][107][108][109][110][111][112][113][114][115]. For example, Zhang et al [116] reported a nanoparticle based "sandwich" detection strategy by immobilizing gold nanoparticles (AuNPs) with reporter probes that flank the target nucleic acids.…”
Section: +mentioning
confidence: 99%
“…To process the CCK-8 assay, MCF-7 cancer cells cultured in the 96-well-microtiter plates were incubated with the obtained nanotheranostic agent (70 µg/mL). After 12 h, MCF-7 cancer cells were washed with PBS buffer, excited under the NIR laser and then incubated for another 24 h. Afterward, the CCK-8 agent (10 µL) was added into each pore and incubated cells for 2 h. Finally, the microplate reader was used to record the absorbance of MCF-7 cancer cells at 450 nm (Yue et al, 2018;Song et al, 2019).…”
Section: Pdt Efficacy Assay In Living Cellsmentioning
confidence: 99%
“…After treatment, MCF-7 cancer cells were collected, stained with apoptosis staining solution for 5.0 min (500 µL binding buffer, 6 µL Annexin V-FITC staining solution and 7 µL PE staining solution) and then injected for flow cytometry analysis. Based on the manufacturer's instruction, the necessary fluorescence compensation was adjusted (Song et al, 2019).…”
Section: Pdt Efficacy Assay In Living Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…UCNPs have been used in different molecular tests including cell and wholebody fluorescent imaging (for instance vascular imaging, 36,37 lymph node imaging, 38 and targeted cancer imaging 39 ). Previous studies have shown that UCNPs coated with different ligands (silica shells, 40 charged polymers, 41 active small molecules, 42 biomacromolecules, 43 etc.) and/or covalently linked to functional groups (peptides, 44 folates, 45 antibodies, 46 etc.)…”
Section: Design Of Up-conversion Nanoprobes For Molecular Imagingmentioning
confidence: 99%